Localization and transcriptional responses of Chrysoporthe austroafricana in Eucalyptus grandis identify putative pathogenicity factors - Mangwanda, Ronishree; Zwart, Lizahn; van der Merwe, Nicolaas A.; Moleleki, Lucy; Berger, David; Myburg, Alexander; Naidoo, Sanushka (Frontiers in Microbiology, 2016)
Chrysoporthe austroafricana is a fungal pathogen that causes the development of stem cankers on susceptible Eucalyptus grandis trees. Clones of E. grandis that are partially resistant and highly susceptible have been identified based on the extent of lesion formation on the stem upon inoculation with C. austroafricana. These interactions have been used as a model pathosystem to enhance our understanding of interactions between pathogenic fungi and woody hosts, which may be different to herbaceous hosts. In previous research, transcriptomics of host responses in these two clones to C. austroafricana suggested roles for salicylic acid and gibberellic acid phytohormone signalling in defense. However, it is unclear how the pathogen infiltrates host tissue and which pathogenicity factors facilitate its spread in the two host genotypes. The aim of this study was to investigate these two aspects of the E. grandis-C. austroafricana interaction and to test the hypothesis that the pathogen possesses mechanisms to modulate the tree phytohormone-mediated defenses. Light microscopy showed that the pathogen occurred in most cell types and structures within infected E. grandis stem tissue. Notably, the fungus appeared to spread through the stem by penetrating cell wall pits. In order to understand the molecular interaction between these organisms and predict putative pathogenicity mechanisms of C. austroafricana, fungal gene expression was studied in vitro and in planta. Fungal genes associated with cell wall degradation, carbohydrate metabolism and phytohormone manipulation were expressed in planta by C. austroafricana. These genes could be involved in fungal spread by facilitating cell wall pit degradation and manipulating phytohormone mediated defense in each host environment, respectively. Specifically, the in planta expression of an ent-kaurene oxidase and salicylate hydroxylase in C. austroafricana suggests putative mechanisms by which the pathogen can modulate the phytohormone-mediated defenses of the host. These mechanisms have been reported in herbaceous plant-pathogen interactions, supporting the notion that these aspects of the interaction are similar in a woody species. This study highlights ent-kaurene oxidase and salicylic hydroxylase as candidates for further functional characterisation.